CULTURAL LITERACY AND THE SPIRIT OF MULTICULTURALISM IN INDONESIA - Sudrajat, Adi; Sufiyana, Atika Zuhrotus (An Natiq, 2024)
Indonesia has extraordinary cultural riches, consisting of various ethnic groups, languages, traditions and customs which are characteristics of the nation that must be protected and preserved. In the midst of the onslaught of modernization and globalization, it is important to strengthen the spirit of multiculturalism, so that national identity and noble values are maintained. This research aims to explore the role of cultural literacy in maintaining the spirit of multiculturalism in Indonesia. Using a qualitative research method such as library research, this research analyzes various relevant literature sources to understand how cultural literacy can promote diversity and tolerance in society. The research results show that cultural literacy plays an important role in increasing understanding and appreciation of cultural differences, which in turn strengthens the spirit of multiculturalism. This research also discusses the challenges faced in implementing cultural literacy and provides recommendations for overcoming these obstacles.